Visual Signal Device (VSD) For Deaf Sports Athletics Malaysia - Pusppanathan, Jaysuman; Jamil Alsayaydeh, Jamil Abedalrahim; Zulkiflli, Nur Amira; Soeed, Kamaruzaman; Zulkapri, Izwyn; Yahya, Azli; Idris, Muhammad Iqbal Tariq; Phang, Fatin Aliah; Nawi, Nina Diana; Mohd Muji, Siti Zarina; Ghazali, Zulkipli; Bain, Mohd Yazid (ISEMT 2019, 2019)
Previous study revealed that the advancement of technology has widen the potential for all individual including the disable to participate in any sport competition. Deaflympic and Malaysia Deaf Games,SOPMA respectively provide the opportunity for the deaf people to compete in sports event internationally and locally. From the literature, it is shown that deaf individuals have some visual-spatial advantages relative to hearing individuals. Hence, in this study, Visual Signal Device (VSD) being developed as a sight-based visual starting system for deaf sports athletes in track and field event. VSD system consist of a RGB LED panel, controller and the SEIKO brand electronic gun. The VSD system were explored to see its effectiveness during the sports for deaf people. The results show that, VSD successfully employed during the recent SOPMA 2018 in Perak, Malaysia